Pembangunan Sistem Monitoring Kualitas Udara Dan Gas Dalam Ruangan Dengan Platform Iot Dan Notifikasi Via Android - Imam Fadli; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Internet of Things (IoT) is a concept to exchange data through the internet with objects that can be controlled remotely. Air is a mixture of gases found in the layers that surround the earth. The component with the most varied such as H20 vapor and carbon dioxide (CO2). Air pollution is defined as the entry of one or more contaminants / pollutants such as dust, smoke, odor, gas, and vapor into the atmosphere in a certain amount and certain characteristics and at a certain time which can endanger the lives of humans, animals, plants, and interfere with comfort in life . This system was designed indoor air and gas quality monitoring on android notifications. The tools consisted of Arduino Mega, MQ2, MQ-7, ZH03A, PZEM 004T, and it was used to detect monitoring air and gas qualityof the air by sending notifications to user with the android smarthphone. The thingspeak.com is used to view monitoring data from sensors. The test results show that the time needed to be able to send android notifications is about 1-3 seconds, while the time needed to send and receive data to thingspeak.com are about 30 seconds. These time can be affected by the internet connection. Sending measurement data by arduino devices is also very good with an average delay less than 300ms. Keywords: Monitoring, air, gas, Iot, Notificaton